1993
DOI: 10.3758/bf03211719
|View full text |Cite
|
Sign up to set email alerts
|

Visual and somesthetic influences on postural orientation in the median plane

Abstract: We investigated optic and somesthetic contributions to perceived body orientation in the pitch dimension. In a within-subject factorial design, each of 12 subjects attempted to set his/her body erect or 45°back from erect while restrained in a movable bed surrounded by an adjustable box. The box provided a visual environment consisting of either a grid pattern, two luminous lines, or complete darkness. Both the grid pattern and the luminous lines were effective at biasing settings of body position when the box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…First, judgments of range and velocity in the exposure condition were more stable than those in the occlusion condition. This result supports the finding of Nemire and Cohen (1993), who showed that body orientation in the median plane is most stable when both visual and somatosensory inputs are available.…”
Section: Effects Of the Visual Verticalsupporting
confidence: 91%
See 1 more Smart Citation
“…First, judgments of range and velocity in the exposure condition were more stable than those in the occlusion condition. This result supports the finding of Nemire and Cohen (1993), who showed that body orientation in the median plane is most stable when both visual and somatosensory inputs are available.…”
Section: Effects Of the Visual Verticalsupporting
confidence: 91%
“…There are a large number of studies concerning cross-modal interaction between vision and postural orientation. Some studies have demonstrated that a stationary (Lackner & Graybiel, 1983;Nemire & Cohen, 1993;Witkin, 1949) or a dynamic (Allison, Howard, & Zacher, 1999;Dichgan, Held, Young, & Brandt, 1972;Higashiyama & Koga, in press;Reason, Mayes, & Dewhurst, 1982) visual pattern alters an observer's postural orientation, and other studies have demonstrated that the postural orientation affects the visual vertical, known as the A-and E-effects, respectively (see Bronstein, 1999, andYardley, 1990, for patients losing vestibular or somatosensory functions, and see van Gisbergen, 2000, andvan Beuzekom, Medendorp, &van Gisbergen, 2001, for normal adults). However, in very few studies have attempts been made to clarify how the visual vertical alters the perceived range and perceived velocity of self-motion.…”
mentioning
confidence: 99%
“…The subjects wore a helmet-mounted ISCAN infrared video system while comfortably seated upright in an adjustable chair with their eyes at the pivot axis of a pitchroom, as depicted in Figure I. The pitchroom (see Nemire & Cohen, 1993) was constructed on an aluminum framework, with its pivot axis at the center of the long side wall; it measured 1.22 X 2.79 X 1.68 m (width X length X height). The framework was fitted with foam-core walls that were coated on their interior sides with wallpaper, providing a grid-within-a-grid pattern consisting of squares that measured 5.2 X 5.2 em, each consisting of64 smaller squares that measured approximately 6.5 mm on each side.…”
mentioning
confidence: 99%
“…Judgments of body tilts (Cohen & Larson, 1974;Nemire & Cohen, 1993;Sigman, Goodenough, & Flannagan, 1979;Witkin, 1949), head tilts (Ebenholtz & Benzschawel, 1977;Wade & Day, 1968), and eye positions (Cohen, Ebenholtz, & Linder, 1995;Matin & Fox, 1989;Matin & Li, 1994;Stoper & Cohen, 1986 vary with changes of visual environment.…”
mentioning
confidence: 99%